Pengaruh Perlakuan Awal terhadap Karakteristik Bioetanol dari Limbah Kulit Singkong Karet (Manihot glaziovii) - Yuniarti, Reni; Satria, Arysca Wisnu; Wiandini, Wandha; Zaezarini, Nabhila; Achmad, Feerzet; Yusupandi, Fauzi (Talenta Publisher (Universitas Sumatera Utara), 2024)
Rubber cassava peel waste (Manihot glaziovii) has a high carbohydrate content, so it is feasible to convert it into bioethanol. In general, bioethanol production consists of four steps, pretreatment, hydrolysis, fermentation, and purification. The purpose of this study was to determine the suitable treatment for obtaining bioethanol with the finest characteristics from rubber cassava peel using three treatment variations, the pretreatment process with variations in the dissolving ratio of sodium hydroxide (NaOH) 0.5 M of 1:10; 1:12.5; and 1:15 (w/v), the hydrolysis process with various concentrations of sulfuric acid (H2SO4) of 0.15 N; 0.30 N; and 0.45 N, and the fermentation process with variations in the fermentation time for 3 days, 7 days, and 9 days. Based on the research results, the highest glucose content was 0.91%, with variations in dissolving NaOH 0.5 M 1:15 (w/v) in the pretreatment process and variations in the concentration of 0.30 N H2SO4 in the hydrolysis process, while the highest ethanol content was 68.05% at a fermentation time of 7 days.